An analytical index relating cutting force to axial depth of cut for cylindrical end mills. (December 2016) - Huang, Weijian; Li, Xi; Wang, Boxing; Chen, Jihong; Zhou, Ji
Abstract: In milling processes, the ever-changing cutting force has great effects on machining quality. A novel cutting force model for cylindrical end mills, discretizing the end mill along its circumferential direction, is described in this paper. An analytical index is established for simplifying the prediction for the cutting force and estimating the fluctuation of it based on the model. The influences of the axial depth of cut on the cutting force and the fluctuation are studied based on the proposed index. The predictions of the analytical index are verified by milling experiments. Highlights: The cylindrical end mill is discretized along its circumferential direction. An analytical index can reflect the fluctuation of the cutting force. An analytical index can simplify the prediction of the cutting force. The cutting force is periodic with the change of the axial depth of cut.